Effect of Waste Plastic as Bitumen Modified in Asphalt Mixture - Abdullah, M.E. (EDP Sciences, 2017)
The objectives of this study are to investigate the engineering properties of the asphalt mixtures containing waste plastic at different percentages i.e. 4, 6, 8, and 10 by weight of bitumen. The experimental tests performed in the study were stability, tensile strength, resilient modulus and dynamic creep test. Results showed that the mixture with 4 plastic has the highest stability (184kN). However, the stability slightly decreases with the increase of plastic additive. On the other hand, the highest tensile strength among the modified asphaltic concrete is 1049kPa (8 plastic added). The modified asphalt mixture with 8 plastic has the highest resilient modulus, which is 3422 MPa (25°C) and 494Mpa (40°C). Where the highest creep modulus recorded is 73.30Mpa at 8 plastic added. It can be concluded that the addition of 8 plastic gave the highest value properties of asphalt mixture. Finally, it can be said that 8 plastic is the optimum value adding. © The Authors, published by EDP Sciences, 2017.